2018
DOI: 10.3390/inorganics6010027
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Protic Imidazolylidene NHC Complexes of Cp*IrCl+ and Cp*RhCl+ with a Pyridyl Tether Formed at Ambient Temperature

Abstract: Protic NHC (PNHC) complexes with N 1 H, N 2 -alkyl/aryl imidazolylidene ligands are relatively rare, and routes for their synthesis differ from what is used to make non-protic analogs. Prior work from our group and others showed that in the presence of a tethering ligand (phosphine or in one case, pyridine), CpM and Cp*M (M = Ir, Ru) PNHC complexes could be made by heating. Here, we find that the use of ionizing agents to activate [Cp*M III Cl(µ-Cl)] 2 (M = Ir, Rh) allows for what we believe is unprecedented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While such N -protonation , and N -alkylation reactions have been demonstrated with various azolato complexes, the instability of [ 2 ] might be problematic requiring previous modifications at the ligand. However, [ 2 ] itself is a potential pre-catalyst for a variety of bifunctional catalyses such as hydrogenation and hydrogen-borrowing reactions. …”
Section: Discussionmentioning
confidence: 99%
“…While such N -protonation , and N -alkylation reactions have been demonstrated with various azolato complexes, the instability of [ 2 ] might be problematic requiring previous modifications at the ligand. However, [ 2 ] itself is a potential pre-catalyst for a variety of bifunctional catalyses such as hydrogenation and hydrogen-borrowing reactions. …”
Section: Discussionmentioning
confidence: 99%
“…26 Grotjahn and coworkers revealed that Rh and Ir complexes with pNHC ligands were effective catalysts for the transfer hydrogenation (TH) of acetophenone and chalcone. 27,28 Furthermore, Song and coworkers demonstrated that the NH functionality of protic NHC favors fast and selective hydrogenation of alkenone through hydrogen bonding. 29 Hahn and Morris have recently demonstrated a Ru-NNC complex, with pNHC in a pincer ligand, as an efficient catalyst for TH of ketones.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66][67][68][69] These complexes with proton-responsive ligands have shown promising reactivity and selectivity in various catalytic reactions. [70][71][72][73][74][75][76][77] Anionic-naked-N-heterocyclic carbene complexes represent a relatively new and emerging class of compounds obtained from pNHC complexes after deprotonation of the N-H unit and are characterized by negatively charged NHC ligands. [78][79][80][81][82] These complexes have been shown to activate small molecules such as carbon dioxide 83 and dihydrogen.…”
Section: Introductionmentioning
confidence: 99%